Smart home automation with Linux and Raspberry Pi - Goodwin, Steven, 1973- (Technology in action series., 2013)
Smart Home Automation with Linux and Raspberry Pi shows you how to automate your lights, curtains, music, and more, and control everything via a laptop or mobile phone. You'll learn how to use Linux, including Linux on Raspberry Pi, to control appliances and everything from kettles to curtains, including how to hack game consoles and even incorporate LEGO Mindstorms into your smart home schemes. You ll discover the practicalities on wiring a house in terms of both and power and networking, along with the selection and placement of servers. There are also explanations on handling communication to (and from) your computer with speech, SMS, email, and web. Finally, you ll see how your automated appliances can collaborate to become a smart home.